Cross-species comparison of the gut: Differential gene expression sheds light on biological differences in closely related tenebrionids. (April 2018) - Oppert, Brenda; Perkin, Lindsey; Martynov, Alexander G.; Elpidina, Elena N.
Graphical abstract: Highlights: Tribolium castaneum and Tenebrio molitor have different life history traits. RNA-Seq identified 6907 orthologs in the larval gut of the two insects. Unique genes may be related to speciation and environmental adaptation. Abstract: The gut is one of the primary interfaces between an insect and its environment. Understanding gene expression profiles in the insect gut can provide insight into interactions with the environment as well as identify potential control methods for pests. We compared the expression profiles of transcripts from the gut of larval stages of two coleopteran insects, Tenebrio molitor and Tribolium castaneum . These tenebrionids have different life cycles, varying in the duration and number of larval instars. T. castaneum has a sequenced genome and has been a model for coleopterans, and we recently obtained a draft genome for T. molitor . We assembled gut transcriptome reads from each insect to their respective genomes and filtered mapped reads to RPKM > 1, yielding 11, 521 and 17, 871 genes in the T. castaneum and T. molitor datasets, respectively. There were identical GO terms in each dataset, and enrichment analyses also identified shared GO terms. From these datasets, we compiled an ortholog list of 6907 genes; 45% of the total assembled reads from T. castaneum were found in the top 25 orthologs, but only 27% of assembled reads were found in the top 25 T. molitor orthologs. There were 2281 genes unique to T. castaneum, and 2088 predicted genes unique to T. molitor, although improvements to the T. molitor genome will likely reduce these numbers as more orthologs are identified. We highlight a few unique genes in T. castaneum or T. molitor that may relate to distinct biological functions. A large number of putative genes expressed in the larval gut with uncharacterized functions (36 and 68% from T. castaneum and T. molitor, respectively) support the need for further research. These data are the first step in building a comprehensive understanding of the physiology of the gut in tenebrionid insects, illustrating commonalities and differences that may be related to speciation and environmental adaptation.